PERLINDUNGAN KONSUMEN ATAS TERJADINYA PERJANJIAN JUAL BELI OKSIGEN SECARA DROPSHIPPING MELALUI FACEBOOK DI KOTA PONTIANAK - Candra, Heri; asikin, uti; karlina, dina (Faculty of Law, Universitas Tanjungpura, 2023)
Abstrac This thesis discusses dropshipping on oxygen buying and selling through Facebook in Pontianak City. The method of buying and selling online by means of dropshipping is more profitable with a 0% risk of loss for not stocking goods, not even shipping. All these responsibilities are carried out by suppliers to consumers on behalf of Dropship. Apart from housewives, teenagers, school children can also make buying and selling transactions using this method because they consider this transaction easy, practical and time-saving. This transaction can be done using social media such as Facebook on a smartphone. The practice of dropshipping also occurs in the sale and purchase of oxygen, which during this pandemic has become one of the necessities for Covid-19 sufferers.The formulation of the problem in this research is